Kinetic Study of the Removal of Methyl Orange Dye by Coupling WO3/H2O2 - N’goran Sévérin Eroi; Aimé Serge Ello; Donourou Diabaté; Konan Roger Koffi (Journal of Chemistry)
In the present work, the heterogeneous Fenton-like process was employed to investigate the kinetic models of the degradation of methyl orange (MO) using tungsten oxide/hydrogen peroxide couple. Tungsten oxide particles were successfully synthesized by reflux without surfactant and characterized by using XRD, SEM, TEM, and FT-IR techniques. The influence of parameters such as temperature and concentration of MO was studied and pseudo first-order and second-order models were applied. WO3/H2O2 showed high efficiency in the removal of methyl orange and attained more than 92.8% in 180 min. The first-order kinetic model was described by the removal process with the correlation coefficient of R2 = 0.99.